Gambaran Asupan Zat Besi, Pengetahuan Gizi, Tingkat Pengetahuan Gizi dan Tingkat Pendidikan Ibu pada Kejadian Anemia Ibu Hamil di Wilayah Kerja Puskesmas Rantau Badak Tanjung Jabung Barat - Dewi, Selvia Ratna; Chandra, Filius; Iswanto, Iswanto (Prosiding Seminar Kesehatan Nasional, 2024)
Anemia in pegnant mother is the condition of the mother with hemoglobin levels below 12 mg/dl, anemia is one of the risks of maternal death, the incidence of babies with low birth weight (LBW), Iron deficiency can cause interference or inhibition of fetal grawth both body cells and brain cells. This study animed to determine the description of subtansce intake, nutritional knowledge and education level of mother toward pregnant mother anemia at working area the public health center Rantau Badak Tanjung Jabung Barat regerency. This study used descriptive design, it was conducted at the public health center Rantau Badak Tanjung Jabung Barat regerency in March 2022. Populasion were all of pregnant mothers as many as 20 people. The collecting of data used questionnaire.